METHODICAL FOUNDATIONS OF INTRODUCING ECO-INNOVATIONS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF RURAL AREAS - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Nozhenko, Yu. M.; Ruban Yи. O. (Scientific Progress & Innovations, 2020)
Taking into account the fact that improving life quality of the country’s population and providing conditions for healthy way of life have the highest state priority and are included practically in all social parts of Governmental and regional target programs, the ways of their solving require further detailed studying. In particular, the problem has been remaining insufficiently investigated concerning the interdependence of various processes connected with market transformations in rural areas and the transition of rural settlements to balanced and effective functioning in the conditions of environmentally friendly settlements based on clear Government investment policy in this field. Moreover, the necessity arises in complex study including ecological (environmental condition), social (the quality of people’s life), and economic (incomes of the population and country on the whole) aspects of the question. That is why environmental and economic evaluation of territories at the regional and inter-regional levels was conducted in order to determine the directions for improving the quality of people’s life by using market innovations like eco-villages. A model of environmental and economic territory assessment has been proposed in the paper. The model reflects environmental and economic dependencies “natural loss – social, environmental, and economic factors” and is a system of simultaneous econometric equations. Based on the obtained economic-mathematical model, the generalizing assessment of economic loss at environmental pollution for the regions of Ukraine was conducted. The system of choosing selective loss minimizing decisions, based on integral loss evaluation in case of environmental pollution was developed taking into account economic factors. Such system can be used to harmonize the interests of environmental and economic security with the aim of creating eco-villages and it can also be used by the regional administrative bodies controlling environmental protection and economic departments as a tool of choosing the most promising strategies, which give the highest social and economic effect in environmentally safe economic development of areas.